SINTESIS DAN KARAKTERISASI NANOKOMPOSIT TIO2-SELULOSA DARI LIMBAH AMPAS TEBU - Cindhy Novita Sari; Dina Kartika Maharani (Unesa Journal of Chemistry, 2025)
Sugarcane bagasse is an abundant agricultural waste in Indonesia, reaching more than 750,000 tons annually, yet it remains underutilized. It contains a high cellulose content of up to 52.7%, one of the highest among agricultural residues. Considering its high fiber content and wide availability, sugarcane bagasse has significant potential to be recycled into high-value materials, including nanocellulose, a nanoscale biopolymer with high surface area, mechanical strength, and crystallinity. This study explores the utilization of cellulose derived from sugarcane bagasse, which was subsequently composited with titanium dioxide (TiO₂) nanoparticles to form nanocomposites. Cellulose isolation was carried out using a combined chemical and mechanical method involving alkali treatment, bleaching, and acid hydrolysis, followed by ultrasonication. The nanocomposite synthesis was performed through a wet dispersion method using a water–ethanol mixture. XRD analysis confirmed the successful isolation of nanocellulose, as indicated by an increase in crystallinity index from 51.37% to 70.55% after isolation, with crystal sizes in the nanometer range, that is 4.31 nm for nanocellulose and 35.41 nm for the nanocomposite. FTIR characterization corroborates the success of isolation, showing a decrease in the intensity of functional groups associated with amorphous components such as C=O and aromatic C=C, from 0.0181 to 0.0131 and from 0.0314 to 0.0140, respectively.